Supplementation of Diets With Bovine Colostrum Influences Immune and Gut Function in Kittens - Gore, Asa M.; Satyaraj, Ebenezer; Labuda, Jeff; Engler, Robyn; Sun, Peichuan; Kerr, Wendell; Conboy-Schmidt, Lisa (Frontiers in Veterinary Science, 2021)
In its early life a kitten faces many significant events including separation from its mother, re-homing and vaccination. The kitten is also slowly adapting to their post-weaning diet. Recent advances in companion animal nutrition have indicated that functional ingredients such as colostrum can help support the immune system and gastrointestinal health. Here we report for the first time the effect of feeding a diet containing 0.1% spray dried bovine colostrum (BC) to growing kittens on gut-associated lymphoid (GALT) tissue responses, systemic immune responses, and on intestinal microbiota stability. BC supplementation induced increased faecal IgA expression, and a faster and stronger antibody response to a rabies vaccine booster, indicative of better localised and systemic immune function, respectively. BC supplementation also helped to maintain kittens’ intestinal microbiota stability in the face of a mildly challenging life event. These results show that BC supplementation can help strengthen the immune system and enhance the gut microbiota stability of growing kittens.